The village beyond the mist - Kashiwaba, Sachiko, 1953- (Restless Books, 2025)
"A mountain town that's not on any map, a messy bookstore with infinite doors, and a spoiled prince under a forgetful wizard's curse . . . this summer might hold more than Lina bargained for! When a gust of wind carries off her umbrella, it leads Lina down a secret path between the trees to a strange and incredible world. In the hidden village of Misty Valley, centaurs roam the cobblestone streets and gnomes visit shops stuffed with spellbooks and enchanted desserts. All magic has a dark side, though, and sometimes even sorcerers need a human's helping hand."